The impact of smart checklist implementation on bedside handover quality: A quasi-experimental study - Ari Sukma Nela; Armen Patria; Nova Nurwinda (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Bedside handover of patients in inpatient rooms is an important element in the continuity of nursing care. Suboptimal bedside handover quality often leads to ineffective communication and potential risks to patient safety. The implementation of a smart checklist as a structured tool is expected to improve the quality of bedside handover by primary nurses. Purpose: To investigate the effect of smart checklist implementation on the quality of bedside handovers. Method: A quasi-experimental design with a pretest–posttest control group was employed. Twelve primary nurses were recruited through total sampling based on inclusion criteria. Bedside handover quality was assessed using a validated questionnaire encompassing information completeness, communication clarity, patient involvement, and timeliness, alongside observation sheets documenting checklist use. Data were analyzed using paired and independent t-tests, with statistical significance set at p < 0.05. Results: The intervention group demonstrated a significant improvement in bedside handover quality following smart checklist implementation, whereas no significant changes were observed in the control group. Conclusion: Smart checklist utilization positively influences the quality of bedside handovers by primary nurses. Routine adoption of this tool is recommended to strengthen communication, patient engagement, and safety in inpatient care settings.